Catching the second wave: clinical characteristics and nosocomial infection rates in major trauma and orthopaedic patients during the COVID-19 pandemic. (2021) - Ajayi, B.; Trompeter, A. J.; Umarji, S.; Saha, P.; Arnander, M.; Lui, D. F.
No abstract available